2023
DOI: 10.1088/1361-6641/acca9d
|View full text |Cite
|
Sign up to set email alerts
|

GaN-based power high-electron-mobility transistors on Si substrates: from materials to devices

Abstract: Conventional silicon (Si)-based power devices face physical limitations—such as switching speed and energy efficiency—which can make it difficult to meet the increasing demand for high-power, low-loss, and fast-switching-frequency power devices in power electronic converter systems. Gallium nitride (GaN) is an excellent candidate for next-generation power devices, capable of improving the conversion efficiency of power systems owing to its wide band gap, high mobility, and high electric breakdown field. Apart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 441 publications
0
6
0
2
Order By: Relevance
“…It is important to note that epitaxial NbTiN films could be grown on Si wafers, which can benefit the CMOS compatibility of functional nitrides. 16 To further reveal the crystal structures of NbTiN films, a Raman spectroscopy study was carried out (see Figure 3). In an ideal rock-salt crystal without any defects or impurities, firstorder Raman scattering is forbidden by inversion symmetry.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that epitaxial NbTiN films could be grown on Si wafers, which can benefit the CMOS compatibility of functional nitrides. 16 To further reveal the crystal structures of NbTiN films, a Raman spectroscopy study was carried out (see Figure 3). In an ideal rock-salt crystal without any defects or impurities, firstorder Raman scattering is forbidden by inversion symmetry.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is indicated that the NbTiN/YAO film has higher degrees of mosaicity and twisting of crystallites than those for the NbTiN/MgO film due to large lattice mismatch epitaxy. It is important to note that epitaxial NbTiN films could be grown on Si wafers, which can benefit the CMOS compatibility of functional nitrides …”
Section: Resultsmentioning
confidence: 99%
“…2(a)-(f). The biosensor is fabricated on a silicon substrate to slash the cost of production and other inherent advantages [54], [55]. The epitaxial structure consists of a aluminum nitride (AlN) nucleation layer of thickness 50 nm followed by a thick doped GaN buffer layer of thickness 3.9 µm and thin Al 0.25 Ga 0.75 N layer of thickness 15 nm.…”
Section: B Fabrication Of Platform Devicesmentioning
confidence: 99%
“…It also has many applications in optoelectronic devices, power devices, transistors, water splitters, catalysis, etc. [11][12][13][14][15][16][17][18][19] Therefore, both MoS 2 and GaN semiconductors have great potential for electronic and optoelectronic applications in the future. In addition, further integration of 2D MoS 2 and GaN semiconductors obtains GaN/MoS 2 heterostructure, which can be explored for more novel applications, such as photocatalytic water splitting, gas sensors, photodetectors, etc.…”
Section: Introductionmentioning
confidence: 99%